Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian (Studi Pada UMKM Pak Dj Oleh-oleh Khas Jambi) - Muhammad Novaldi; Arsa Arsa; Anzu Elvia Zahara (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the influence of product quality and promotion on the decision to purchase at MSMEs by Pak Dj Khas Jambi. As the goal is to find out the quality of products and promotion of the decision to purchase by Mr. Dj Typical Jambi. The research method used in this study uses descriptive quantitative methods and the data analysis method uses t-test, f-test, R Square test, Multiple Linear Regression. The sample in this study were 85 respondents who were taken from some of the people in the city of Jambi. The results of this study indicate that product quality (X1) has a significant influence on purchasing decisions. Promotion (X2) is also very significant on purchasing decisions. Based on the F Test the of Product Quality (X1) and Promotion (X2) simultaneously have the same on Purchase Decisions (Y).